A vision for the sending of the Church in Botswana - Henry, Desmond (2011)
The purpose of this article was to present a vision (of a preferred future) for the southern African ecclesia, based on an accurate understanding of what can be termed a missional ecclesiology. This concept was explored using the current context of my ministry, that of the Republic of Botswana, as a primary interlocutor.
Keywords: Missional; Ecclesiology; Missio Dei; Postmodern